Analysis of Spatial Vibration on Scanning Mirror Imaging Based on Frequency Filtering - Ziqi Yu; Li Jiang; Zhihai Yao (IEEE Access, 2021)
In order to analyze the impact of multisource vibration on the imaging quality of aerospace optical payload during camera scanning, a dynamic imaging quality degradation model fused with satellite vibration filter templates is established. Firstly, according to the motion scanning process of the TDI camera, a filter template combining the amplitude and frequency of the vibration source is designed; Secondly, a piecewise function of satellite vibration with a frequency range of 1 Hz to 1000 Hz is obtained by curve fitting, and the amplitudes of different frequency ranges are brought into the image filter template to simulate the output image affected by the vibration. Finally, the output degraded image is analyzed through structural similarity and mean square error. The simulation results show that during the imaging process of the aerospace scanning mirror, the line frequency of the camera changes regularly with the scanning speed. When platform vibration frequency is similar to the camera’s exposure frequency, it will have a large impact on image quality. Therefore, when the camera’s exposure frequency is 110 Hz, vibration at a frequency of 110 Hz will further degrade the image quality. This article is expected to provide guidance for spatial vibration suppression and image quality degradation assessment in the imaging process of aerospace scanning mirrors.